2015
DOI: 10.14740/gr686w
|View full text |Cite
|
Sign up to set email alerts
|

Slower Fibrosis Progression Among Liver Transplant Recipients With Sustained Virological Response After Hepatitis C Treatment

Abstract: BackgroundThe natural course of hepatic fibrosis in HCV allograft recipients with sustained virological response (SVR) after anti-HCV therapy remains debatable. The aim of this study was to examine the progression of fibrosis in a cohort of patients who achieved SVR compared with those without treatment.MethodsThe 167 patients who met the inclusion and exclusion criteria were chosen from a transplant database. All patients were required to have histological evidence of recurrent HCV infection post-liver transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Treatment of HIV with antiretroviral therapy and treatment of HCV have independently been shown to delay the progression of fibrosis and end‐stage liver disease among coinfected patients . However, the rates of SVR with immune‐based methods based on peginterferon (PEG‐IFN) and ribavirin therapy have been significantly inferior among coinfected patients compared to patients monoinfected with HCV, the reasons for which have not been fully elucidated .…”
mentioning
confidence: 99%
“…Treatment of HIV with antiretroviral therapy and treatment of HCV have independently been shown to delay the progression of fibrosis and end‐stage liver disease among coinfected patients . However, the rates of SVR with immune‐based methods based on peginterferon (PEG‐IFN) and ribavirin therapy have been significantly inferior among coinfected patients compared to patients monoinfected with HCV, the reasons for which have not been fully elucidated .…”
mentioning
confidence: 99%
“…Importantly, we recognized no serious harmful effects on transplant function, as no patient experienced an episode of acute cellular rejection or required re-transplantation during or immediately after the antiviral therapy. Most patients showed improvement of liver function after the end of therapy, which might improve graft survival in the future[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both patients had recurrent cirrhosis and were transplanted more than 5 years ago. These patients might represent a subgroup of patients that have reached a point of no return, as HCV infection has already caused severe damage to the liver graft, which cannot be reverted even by successful antiviral therapy[ 29 - 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using paired biopsies in this patient population were limited, variable, and mainly from patients treated with interferon-based therapies; patients in these studies were also at variable times post SVR. (27,(32)(33)(34) The population selected in the post-liver transplant state should have been those who had inflammatory activity leading to and perpetuating fibrosis. In contemporaneous studies, emricasan was shown to have negligible effects on NASH in multiple cohorts-those with NASH, compensated NASH cirrhosis, and decompensated NASH cirrhosis.…”
Section: Original Article | 11mentioning
confidence: 99%